Evolutive emergence and divergence of an Ig regulatory node: An environmental sensor getting cues from the aryl hydrocarbon receptor? - D'Addabbo, Pietro; Frezza, Domenico; Sulentic, Courtney E.W. (Frontiers in Immunology, 2023)
One gene, the immunoglobulin heavy chain (IgH) gene, is responsible for the expression of all the different antibody isotypes. Transcriptional regulation of the IgH gene is complex and involves several regulatory elements including a large element at the 3' end of the IgH gene locus (3'RR). Animal models have demonstrated an essential role of the 3'RR in the ability of B cells to express high affinity antibodies and to express different antibody classes. Additionally, environmental chemicals such as aryl hydrocarbon receptor (AhR) ligands modulate mouse 3'RR activity that mirrors the effects of these chemicals on antibody production and immunocompetence in mouse models. Although first discovered as a mediator of the toxicity induced by the high affinity ligand 2,3,7,8-tetracholordibenzo-p-dioxin (dioxin), understanding of the AhR has expanded to a physiological role in preserving homeostasis and maintaining immunocompetence. We posit that the AhR also plays a role in human antibody production and that the 3'RR is not only an IgH regulatory node but also an environmental sensor receiving signals through intrinsic and extrinsic pathways, including the AhR. This review will 1) highlight the emerging role of the AhR as a key transducer between environmental signals and altered immune function; 2) examine the current state of knowledge regarding IgH gene regulation and the role of the AhR in modulation of Ig production; 3) describe the evolution of the IgH gene that resulted in species and population differences; and 4) explore the evidence supporting the environmental sensing capacity of the 3'RR and the AhR as a transducer of these cues. This review will also underscore the need for studies focused on human models due to the premise that understanding genetic differences in the human population and the signaling pathways that converge at the 3'RR will provide valuable insight into individual sensitivities to environmental factors and antibody-mediated disease conditions, including emerging infections such as SARS-CoV-2.